STAKLENI VRČEVI I POSUDE ZA POHRANU IZ ARHEOLOŠKOG MUZEJA ISTRE - IZBOR. - STARAC, Alka (Histria Archaeologica, 2024)
This paper discusses single-handled and two-handled glass jugs, bottles with rounded and cylindrical bodies, jars, urns, and lids from the Roman Period Collection of the Archaeological Museum of Istria; in all 65 artefacts of which almost half have not seen prior publication. For the most part these are intact showpiece artefacts from the museum’s permanent exhibition, for one third of which we have no data concerning the findspot. Most of the selected glassware types were free-blown. Some of the jugs and bottles were mould-made, but lack inscriptions and maker’s marks. The artefacts are identified in terms of the chronology and typology, and compared with similar artefacts found in the immediate vicinity of Istria, thus complementing our knowledge of manufacturing and commercial flows in Roman period Istria.